Intellection of upbringing in global context of present and future challenges in pedagogy - Dubovicki, Snježana (Array, 2019)
Intellection of upbringing in the global context of science that deals with theoretical and practical research in the field of upbringing and education at all levels has brought about a revival. Traditional teaching, which pays more attention to education and less to upbringing, has led to a partial diminishing in the importance of upbringing at higher levels of education, especially in a university context. Various translations of works from other languages into English, often translating upbringing as education, also contributed to this. In order to give upbringing a place it deserves in the university teaching, and to equate it with education in a university context, we considered social forms as potential preconditions for “returning” the presence of upbringing activities to the university level. By looking at this issue through the teaching process, it was important to emphasize the contribution of pedagogy workshop to encouraging the upbringing function of teaching. We have distinguished the pedagogy workshop from other social forms because participation in it equally affects the sensory, emotional, and moral functions of all participants in the teaching process (and not just intellectual ones), which were important in the research of the role of upbringing. Previous research has shown that creative university teaching contributes to fostering the educational role of teaching and helps self-actualization, which is beneficial for all participants in the teaching process.